Analisis Kinerja Keuangan Pemerintah Daerah Kota Samarinda Tahun 2020-2024 - Muhammad Gading Setiawan; Mega Tanjung Hapsari; Nastwa Alodia Putri Ananta; Mia Fazira; Rofiqoturrohmah Rofiqoturrohmah; Fitriani Eka Hariyati (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2026)
Regional autonomy requires local governments in Indonesia to have the ability to manage their finances efficiently and independently. This study aims to determine the financial performance of the Samarinda City Government during the 2020–2024 period by looking at the income growth ratio, dependency, independence, degree of decentralization, and effectiveness of local revenue (PAD). Secondary data from the Budget Realization Report (APBD). This study uses a quantitative descriptive method. The results show that the average revenue growth was only 14.40% (low category), the financial dependency ratio was very high at 54.92%, the resilience ratio was low at 35.75%, and the degree of decentralization was low at 19.50%. On the other hand, PAD is considered very effective with an average of 112.79%. According to these findings, although PAD shows good results, the fiscal independence of Samarinda City is still weak because it is highly dependent on central transfers. Therefore, to maintain fiscal independence and sustainability, local governments must strengthen plans to increase and expand revenue sources.